Gojri Grammar - Sharma, J.C. (My University, 1982)
The organization of the grammar is based on grammatical functions rather than on grammatical forms. This will help the new learner to find easily how the different functions, which he already knows and wants to express, are formalized in this language. Since this Grammar is primarily meant for pedagogical purposes, theoretical discussions and justifications for a particular analysis are kept to a minimum. Grammar is divided generally into two broad categories of noun morphology and verb morphology. A description of adjectives and adverbs follows verb morphology. A description of adjectives and adverbs follows verb morphology. The chapter on syntax describes the order of the constituents at the surface level.
Keywords: Gojri